The Map Media Development of Changes to the Musi River Border in Palembang - Murjainah; Setianto Heri; Mujib Muhammad Asyroful (E3S Web of Conferences)
This study aims to produce a map of the Musi River border changes in Palembang which is worthy of learning geography in hydrology courses. The method used in this research is a development research method by adopting the Alessi and Trolip development model which consists of planning, design, and development stages. The data collection techniques used in this study were interviews, questionnaires, and documentation. Data analysis using qualitative descriptive analysis techniques. Based on the results of the analysis of the map of the development of the media for changing the boundaries of the Musi Palembang river, it shows that the product developed is very worthy for learning after going through the alpha test, both the analysis results of the validator from media experts and material experts. Meanwhile, the beta test phase and product field trials are worthy to use for students of geography education.